Effect of oxygen gas exposure on T91 alloy at high temperature oxidation of steam reformer - Rosdin, Muhammad Rafiq Haikal; Ismail, Ahmad Abdul Mun'im; Abdul Hamid, Abd. Malek; Purwanto, Hadi; Illias, Suhaimi; Syed Abu Bakar, Syed Noh; Ani, Mohd. Hanafi (Springer, 2023)
Steam-Methane Reforming (SMR) is one of the most economical ways to produce hydrogen from natural gas. Steam reforming industry is hugely relied on using supercritical power plant where the working temperature of the plant must exceed 600 °C. Along with the high operating temperature, the situation promotes the acceleration of high temperature oxidation. This will cause fouling and spalling of oxide scales at the boiler tube. Eventually, fouling will reduce heat transfer between the tube and steam generated, causing a higher temperature is needed to produce steam. Until now, the only approach used by the industry is to manually replace the corroded boiler tube. Other than that, many studies have been conducted on the behavior of boiler tubes at temperatures exceeding 800 °C. However, to our knowl- edge, no study has been done to investigate the air electrolyte substrate interfacial electrochemical reaction at high temperature. This project was carried out to inves- tigate the corrosion potential of T91 boiler tube at 650 °C for 2 h, 8 h, and 12 h, measure the current density (Icorr) by calculating corrosion potential (Ecorr) value using Tafel Extrapolation and determine the oxidation potential of oxygen gas at 650 °. The oxide layer thickness at exposed temperature was determined to measure the oxidation kinetics. The study concludes that there was an increase of 8.49% in current conductivity between the blank experiment and T91 alloy oxidation potential test. The oxidation process was following the parabolic rate law which manifest that the corrosion is controlled by ionic diffusivity in the oxide layer. The oxide layer formed on the sample has an average thickness of 54.10 μm and this value can be used to calculate the oxidation kinetics of the sample using parabolic rate constant, Kp, resulting with the value of 6.78 × 10−14 m2/s.